Measuring the Consistency of Liquidity and its Financial Health: A Study on Tribal Co-operative Marketing Development Federation of India - P. Chellasamy; S. Kannamudaiyar (Jurnal Multidisiplin Madani, 2024)
The present study of the paper aims to show the consistency of the liquidity and its effects on the financial health of Tribal Co-operative Marketing Development Federation of India (TRIFED). The objective of the study is to examine the extent of association between the variables and to show the consistency of the liquidity position of the TRIFED. For examining the significance of the value of W, Chi-square (χ2) and Altman’s Z-score has been used to check the organization monetary position.  The result of the analysis concludes that Kendall’s coefficient of concordance (W) among the given six ratios are found to be statistically significant at the 5 % level. In addition, one sample t-test portray a remarkable difference in the Altman’s Z-score of Tribal Co-operative Marketing Development Federation of India (TRIFED) during the study period. The study leads to significant conclusion based on the study’s result